Application of the Buerger Allen Exercise (BAE) in Lowering Blood Glucose Levels In Mrs. S With Diabetes Mellitus In Sukoanyar Village, Pakis District, Malang Regency - Dini Nurbita; Zaqqi Ubaidillah (Asosiasi Dosen Muda Indonesia, 2026)
Diabetes mellitus is a metabolic disorder characterized by persistent hyperglycemia caused by impaired insulin secretion, ineffective insulin action, or both. In addition to pharmacological treatment, supportive non-pharmacological interventions are needed to help control blood glucose levels, especially in patients with circulation problems. Objective: This study aimed to determine the effect of Buerger Allen Exercise (BAE) therapy on reducing blood glucose levels in a patient with diabetes mellitus in Sukoanyar Village, Pakis District, Malang Regency. Method: This study used a qualitative approach with a case study design. Data were collected on May 3–8, 2025. The subject was selected using purposive sampling. Buerger Allen Exercise therapy was administered for 15 minutes over six consecutive days based on the standard operating procedure, and blood glucose levels were measured after each session. Findings: The results showed that the implementation of Buerger Allen Exercise therapy contributed to a reduction in blood glucose levels in the patient with diabetes mellitus. Implications: These findings indicate that Buerger Allen Exercise may be used as a supportive non-pharmacological intervention in diabetes management, particularly in community-based nursing practice. Originality: The originality of this study lies in the application of Buerger Allen Exercise as a simple, low-cost, and practical nursing intervention in a real community setting.